2017
DOI: 10.1111/plb.12561
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lunisolar tidal acceleration on stem elongation growth, nutations and leaf movements in peppermint (Mentha × piperita L.)

Abstract: Orbital movement of the Moon generates a system of gravitational fields that periodically alter the gravitational force on Earth. This lunar tidal acceleration (Etide) is known to act as an external environmental factor affecting many growth and developmental phenomena in plants. Our study focused on the lunar tidal influence on stem elongation growth, nutations and leaf movements of peppermint. Plants were continuously recorded with time-lapse photography under constant illumination as well in constant illumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…It is commonly thought that nutations in individual plants show independent kinetics and trajectories of movements; thus, nutation is not only species dependent, but it is also an individual trait. However, in our previous experiments (Zajączkowska & Barlow ) we found that although peppermint ( Mentha × piperita L.) plant apices, analysed at one time, were characterised by a variable nutation velocity, they all showed similarity of movement dynamics, that correlated with changes in the lunisolar tidal acceleration (Etide). This correlation confirms that plants are affected by shifts in the gravitational field, caused by the Moon's position in relation to that of Earth (Endres & Schad ; Fisahn et al .…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…It is commonly thought that nutations in individual plants show independent kinetics and trajectories of movements; thus, nutation is not only species dependent, but it is also an individual trait. However, in our previous experiments (Zajączkowska & Barlow ) we found that although peppermint ( Mentha × piperita L.) plant apices, analysed at one time, were characterised by a variable nutation velocity, they all showed similarity of movement dynamics, that correlated with changes in the lunisolar tidal acceleration (Etide). This correlation confirms that plants are affected by shifts in the gravitational field, caused by the Moon's position in relation to that of Earth (Endres & Schad ; Fisahn et al .…”
Section: Introductionmentioning
confidence: 82%
“…The trajectories of stem tip movement, considered to be a specific ‘track’ of an individual plant, can thus provide valuable data on the dynamic states of a plant, for example, by providing important information on plant growth rates. Initial evidence for the importance of a detailed mathematical analysis of plant nutational movements emerged from the results of our previous study, which revealed a close relationship between the velocity of nutational movement and the growth rate of the mint stem (Zajączkowska & Barlow ). This preliminary finding can now be substantiated due to the newly developed mathematical toolbox by the results presented here.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…But such rhythms may be biological in origin (for examples see, Reinberg et al 2016;Zajączkowska and Barlow 2017). Indeed, some older studies noticed how, for example, the presence of ice nucleating particles also varied with the lunar cycle (Bigg 1963;Bigg and Miles 1964).…”
Section: New Insightsmentioning
confidence: 99%
“…More recently, Peter's interests turned towards the moon and the influence that this satellite may have on biological phenomena on Earth [99]. That conference presentation was followed up by many papers investigating the influence of the moon on such plant phenomena as leaf movements [99][100][101], stem elongation [102], fluctuations in diameters of tree stems [103], root growth [104][105][106], emissions of biophotons by seedlings [107][108][109][110], and chlorophyll fluorescence [111]. Not constrained by gravity, Peter was also developing ideas about extraterrestrial influences and plant bioelectricity [112].…”
Section: Extra-terrestrial Influences On Plant-lifementioning
confidence: 99%